EVALUATION OF PATIENT-SPECIFIC QUALITY ASSURANCE (PSQA) USING OCTAVIUS 4D IN IMRT PLANNING FOR NASOPHARYNGEAL CANCER CASES - Endarko, Endarko; Rahayu, Rizki Budi; Alifiani, Rustika; Hariyanto, Aditya Prayugo; Almira, Levina (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2026)
Patient-Specific Quality Assurance (PSQA) is an important procedure for verifying the accuracy of dose planning before administering radiation therapy to patients. This study aimed to evaluate the suitability of dose distribution in three variations of IMRT plans for nasopharyngeal cancer cases in two patients using the PTW Octavius 4D phantom and Verisoft software. Three irradiation plans were created based on variations in the optimization objectives for organ risk at the TPS, namely Plan0 (no optimization), Plan1 (moderate priority optimization for the parotid gland, brainstem, and spinal cord), and Plan2 (high priority optimization for the parotid gland, brain stem, and spinal cord). PSQA measurements were performed using a gamma index with criteria of 3%/3 mm, 3%/2 mm, and 2%/2 mm. The fluence map results showed that all irradiation plans had fluence patterns consistent with the TPS calculations without significant deviations in areas outside the target. The gamma passing rate (GPR) values for the 3%/2 mm criterion were 97.1−99.8% for Plan0, 96.1%−98.6% for Plan1, and 95.5%−99.5% for Plan2, all of which were above the tolerance limit of ≥95% as recommended by AAPM TG-218. For the 2%/2 mm criterion, all plans achieved a GPR above 90%, in accordance with the AAPM TG-119 standard for complex IMRT plans. These results indicate that the linac dose delivery system and MLC movement function consistently and are capable of reproducing the fluence according to TPS calculations. Thus, the use of Octavius 4D as the PSQA standard was effective for verifying the accuracy of IMRT plans in this study, and the 3%/2 mm criterion is recommended as a clinical evaluation parameter.